Pendampingan Pembuatan Kemasan Label Pada UMKM Kerupuk Udang Dan Payus Mak Sah - Femy Atha Fredella; Delta Diva Dinanty; Syahrani Nur Aullia Octivanti; Faridah Nur Azizah; Fairuzah Nafisah Adwitiya (FKIP, Universitas Palangka Raya, 2023)
In the era of globalization, packaging plays a very important role, apart from showing a good appearance the packaging certainly supports the product image, but in fact the labels on the packaging are often ignored by Micro, Small and Medium Enterprises (MSMEs) in Indonesia. MSME actors prioritize the product packaging strategy and ignore other supporting factors, namely labeling. Labels are writing, pictures, or a combination of both that are inserted into, affixed or printed on and form part of the package to provide comprehensive and complete information about the contents of the package. The product packaging strategy uses labeling, namely by placing a combination of writing or images, then placing it as a supporting part in the product packaging to increase interest in a product, it can also make it easier to recognize because the information from the product is placed in an easily visible part. Labeling the product contains information of the product or the brand, it also can be the composition or the certificate of legality. As well as taxes contained in small and medium businesses that can help determine the selling price of an item to be marketed.